Synthesis, Structure, Magnetic and Antibacterial Properties of polymeric [M(Quin)2(N(CN)2)2]∞ (M = Mn(II), Co(II); Quin = quinoline) - I Wayan Dasna; Ubed Sonai Fahruddin Arrozi; Husni Wahyu Wijaya; Sutandyo Dwija Laksmana; Stéphane Golhen (Journal of Mathematical and Fundamental Sciences, 2022)
Two complexes of [Mn(Quin)2(N(CN)2)2]∞ (1) and [Co(Quin)2(N(CN)2)2]∞ (2) were synthesized and characterized. The as-synthesized complexes crystallized in a triclinic lattice with a space group of P-1. The unit cell parameter of 1 was a = 7.5207(14) Å, b = 7.7729(16) Å, c = 9.5968(15) Å, α = 96.388(6) o, β = 112.617(5) o, γ = 102.751(6) o, while for complex 2 it was a = 7.3942(10) Å, b = 7.7960(10) Å, c = 9.4907(13) Å, α = 96.631(4) o, β = 112.742(4) o, γ = 102.458(4) o. The magnetic properties and antimicrobial properties of both polymeric complexes were examined by magnetic susceptibility and diffusion techniques, respectively. Complexes 1 and 2 both showed antiferromagnetic properties and had a higher inhibitory effect on the growth of Staphylococcus aureus than Salmonella typhi.